Modelling the adoption of industrial cogeneration in Japan using manufacturing plant survey data - Bonilla, D; Akisawa, A; Kashiwagi, T (Elsevier, 2003)
Electric power deregulation in Japan opens opportunity for further penetration of on-site generation (cogeneration) otherwise known as distributed generation. In the paper the authors present a survey on Japanese industrial plants to fill existing gaps for the assessment of modern cogeneration (combined heat and power, CHP). The objective of the paper is to empirically examine CHP systems based on cross-sectional binary models; second to review diffusion trends of CHP by system vintage during the 1980–2000 period in the manufacturing sector. The econometric results point that the probabilities of embracing this technology increase, in declining importance, with on-site power consumption, and steam demand, operational hours as well as with payback period, purchased power. For example the survey shows that the CHP is used for the purpose of exporting power rather than meeting the plant’s own consumption. Some of our results are in line with those of Dismukes and Kleit (Resource Energy Econ. 21 (1999) 153) as well with Rose and Macdonald (Energy J. 12(12) (1991) 47). We also find that a unit increase in satisfaction with CHP will lead to a 54% in CHP capacity. We find significant evidence on the cost effectiveness of CHP under conservative assumptions. Regarding the influence of satisfaction and performance indicators for the several plants, the survey threw some unexpected evidence on the nature of CHP.